2011
DOI: 10.1158/0008-5472.can-11-1704
|View full text |Cite
|
Sign up to set email alerts
|

DLL4-Notch Signaling Mediates Tumor Resistance to Anti-VEGF Therapy In Vivo

Abstract: Resistance to VEGF inhibitors is emerging as a major clinical problem. Notch signaling has been implicated in tumor angiogenesis. Therefore, to investigate mechanisms of resistance to angiogenesis inhibitors, we transduced human glioblastoma cells with retroviruses encoding Notch delta-like ligand 4 (DLL4), grew them as tumor xenografts and then treated the murine hosts with the VEGF-A inhibitor bevacizumab. We found that DLL4-mediated tumor resistance to bevacizumab in vivo. The large vessels induced by DLL4-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
187
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(200 citation statements)
references
References 51 publications
13
187
0
Order By: Relevance
“…A previous report showed that Dll4 expressed in tumor cells regulated cancer growth and differentiation (26), and improved tumor vascular function and promoted tumor growth (27,28). Moreover, Zhang and colleagues showed that Dll1-Notch signaling in cancer cells regulates invasion and metastasis in vitro and in vivo (29).…”
Section: Discussionmentioning
confidence: 98%
“…A previous report showed that Dll4 expressed in tumor cells regulated cancer growth and differentiation (26), and improved tumor vascular function and promoted tumor growth (27,28). Moreover, Zhang and colleagues showed that Dll1-Notch signaling in cancer cells regulates invasion and metastasis in vitro and in vivo (29).…”
Section: Discussionmentioning
confidence: 98%
“…Tumor ECs engineered to overexpress DLL4 develop enlarged mature vessels that are resistant against VEGF blockade, while inhibition of Notch signaling restores the sensitivity to antiangiogenic drugs in a xenograft model (83). Resistance can result from activation of FGF2-FGFR and EphB4-Ephrin-B2 pathways or from decreased levels of VEGFR2 (83). Several proangiogenic molecules become upregulated under selective pressure by VEGFIs/ VEGFRIs (79, 84).…”
Section: Successes and Challenges Of Antiangiogenic Drugsmentioning
confidence: 99%
“…Vascular Endothelial Growth Factor (VEGF) stimulates angiogenesis by influencing vessel formation through regulation of proliferation, migration and survival of endothelial cells (1)(2)(3). Blocking VEGF by bevacizumab, a monoclonal antibody, has been proposed to cause inhibition of neovascularization, regression of existing immature micro-vessels, and normalization of abnormal vasculature (4,5); this has consequences for the flux of oxygen, nutrients, metabolites and therapeutic agents, ultimately preventing tumor growth and resulting in tumor shrinkage.…”
Section: Introductionmentioning
confidence: 99%